The abilities in dog pain sign recognition as assessed by presenting seventeen listed dog behavioural signs and three case descriptions to dog owners and non-dog owners - Silvia M. A. Gardeweg; Dionne E. Picard; Ineke R. van Herwijnen (PLoS ONE, 2026)
To investigate abilities and differences in dog pain sign recognition, we assessed these recognition skills in 530 dog owners and 117 non-dog owners through an online questionnaire. We asked participants to score the likeliness of pain relevance for seventeen dog behavioural signs and in three dog behavioural cases. When assessing the seventeen behavioural signs, the signs of ‘change in personality’, ‘hesitant paw lifting’, ‘fluctuating mood’ and ‘reduced play’ were scored at higher pain likeliness scores than ‘air sniffing’, ‘nose licking’ and ‘yawning’. The behaviours of ‘turning the head or body away’ and ‘freezing’ were scored at higher pain likeliness scores by non-dog owners than dog owners. The cases twice regarded behaviours of a dog with a painful condition and once without such a condition. One painful condition came with overt pain signs, related to movement ability once and the other painful condition came with subtle pain signs, such as shadowing family members and restlessness at night. We found that participants rated the likeliness of pain significantly higher in the case describing overt dog pain signs, related to movement ability. Dog owners’ ratings for this case were slightly higher than non-dog owners’ ratings. Yet, for the case describing subtle dog pain signs, such as shadowing and restlessness, no differences were found between dog owners and non-dog owners. This may indicate that dog owners recognise subtle dog pain signs with less ease. Possibly, dog owners recognise signs such as ‘turning head or body away’ and ‘freezing’ (more so) as a stress/fear sign, than as a possible pain sign. We argue that education on dog behaviour may benefit from addressing how behavioural signs may also, or alternatively, be indicative of pain. Our finding that owners of dogs that experienced a painful event, scored a higher likeliness of certain possible pain signs, indicates that experience matters and this underpins how education on dog behaviour could possibly benefit animal welfare through addressing subtle pain signs in dogs.